Sialic Acid Residues Mediate Mycoplasma pneumoniae Attachment to Human and Sheep Erythrocytes - Baseman, J. B. (1982)
The adherence of Mycoplasma pneumoniae to human and sheep erythrocytes was directly related to the presence of sialyl residues on the erythrocytes. Competitive binding studies between M. pneumoniae and M. gallisepticum, known to bind to human erythrocytes via glycophorin, further reinforced the role of sialic acid in this recognition event.